2016
DOI: 10.1371/journal.pone.0166644
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Organ Culture Model to Quantify Collagen Remodeling in Tree Shrew Sclera

Abstract: Increasing evidence suggests that unknown collagen remodeling mechanisms in the sclera underlie myopia development. We are proposing a novel organ culture system in combination with two-photon fluorescence imaging to quantify collagen remodeling at the tissue- and lamella-level. Tree shrew scleral shells were cultured up to 7 days in serum-free media and cellular viability was investigated under: (i) minimal tissue manipulations; (ii) removal of intraocular tissues; gluing the eye to a washer using (iii) 50 μL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 50 publications
0
14
0
Order By: Relevance
“…Genetic analysis does show that the tree shrew is in proximity to primates, 38 and they have been used widely as an alternative model to higher primates for studies of psychosocial stress, 39 hepatitis, 40 and myopia. 33 , 34 However, tree shrews do not appear to share any derived characteristics. Thus, they are now classified independently in the order Scandentia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Genetic analysis does show that the tree shrew is in proximity to primates, 38 and they have been used widely as an alternative model to higher primates for studies of psychosocial stress, 39 hepatitis, 40 and myopia. 33 , 34 However, tree shrews do not appear to share any derived characteristics. Thus, they are now classified independently in the order Scandentia.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the tree shrew ( Tupaia belangeri ) is a small mammal closely related to primates 32 that currently is used in vision research as an inducible myopia model. 33 , 34 Tree shrews are accessible and, most importantly, have a robust connective tissue lamina with horizontally-oriented laminar beams that insert into the peripapillary sclera and, thus, are load-bearing. 35 We validated a novel animal model of glaucoma in tree shrews by demonstrating a reliable method to chronically elevate IOP with resultant selective gradual loss of the RGC and retinal nerve fiber (RNFL) layers, histopathologic evidence of glaucomatous optic neuropathy, and remodeling of the load-bearing connective tissues of the ONHs consistent with human glaucoma.…”
mentioning
confidence: 99%
“…Elsewhere, arguments have been made about the connective tissues of the eye remodeling in response to IOP load changes, 43 with age 29 , 44 and disease. 45 How the collagen of LC beams changes in these conditions remains unknown and should be investigated. Herein we have demonstrated that this can be done using PLM.…”
Section: Discussionmentioning
confidence: 99%
“…The tree shrew has been proposed to be a viable and alternative animal model to primates in disease studies and drug safety testing. Many researchers have recently used the tree shrew to create animal models for studying hepatitis B or C virus infections and myopia as well as social stress and depression (Baldivia et al., 2016; Fuchs, 2005; Norton et al., 2006; Wang et al., 2012; Zhao et al., 2002). Nevertheless, there have been few studies on the otology of tree shrews.…”
Section: Introductionmentioning
confidence: 99%